#1**+5 **

Solve for x:

(x + 1)/2 + (2 x - 3)/9 = 11

Put each term in (x + 1)/2 + (2 x - 3)/9 over the common denominator 18: (x + 1)/2 + (2 x - 3)/9 = (9 (x + 1))/18 + (2 (2 x - 3))/18:

(9 (x + 1))/18 + (2 (2 x - 3))/18 = 11

(9 (x + 1))/18 + (2 (2 x - 3))/18 = (9 (x + 1) + 2 (2 x - 3))/18:

(9 (x + 1) + 2 (2 x - 3))/18 = 11

9 (x + 1) = 9 x + 9:

(9 x + 9 + 2 (2 x - 3))/18 = 11

2 (2 x - 3) = 4 x - 6:

(4 x - 6 + 9 x + 9)/18 = 11

Grouping like terms, 9 x + 4 x - 6 + 9 = (9 x + 4 x) + (9 - 6):

((9 x + 4 x) + (9 - 6))/18 = 11

9 x + 4 x = 13 x:

(13 x + (9 - 6))/18 = 11

9 - 6 = 3:

(13 x + 3)/18 = 11

Multiply both sides of (13 x + 3)/18 = 11 by 18:

(18 (13 x + 3))/18 = 18×11

(18 (13 x + 3))/18 = 18/18×(13 x + 3) = 13 x + 3:

13 x + 3 = 18×11

18×11 = 198:

13 x + 3 = 198

Subtract 3 from both sides:

13 x + (3 - 3) = 198 - 3

3 - 3 = 0:

13 x = 198 - 3

198 - 3 = 195:

13 x = 195

Divide both sides of 13 x = 195 by 13:

(13 x)/13 = 195/13

13/13 = 1:

x = 195/13

The gcd of 195 and 13 is 13, so 195/13 = (13×15)/(13×1) = 13/13×15 = 15:

**Answer: |x = 15**

Guest Jan 29, 2017